2018
DOI: 10.1002/cphc.201800504
|View full text |Cite
|
Sign up to set email alerts
|

Transient Secondary and Tertiary Structure Formation Kinetics in the Intrinsically Disordered State of α‐Synuclein from Atomistic Simulations

Abstract: In the absence of a stable fold, transient secondary structure kinetics define the native state of the prototypical and pharmacologically relevant intrinsically disordered protein (IDP) α-Synuclein (aS). Here, we investigate kinetics preventing ordering and possibly pathogenic β-sheet aggregation. Interestingly, transient β-sheets form frequently at sub μs time scales precisely at the positions observed in aS amyloid fibrils. The formation kinetics competes with rapid secondary structure dissociation rates, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
(71 reference statements)
0
24
0
Order By: Relevance
“…In clusters 1, 2, and 6, the central segment of a-syn has a higher propensity to form b strand than the N-and C-terminal segments. Previous studies suggest that b-strand formation within the hydrophobic central segment may lead to oligomerization and fibril formation (Balupuri et al, 2019;Brodie et al, 2019;Graen et al, 2018;Healey et al, 2016;Jó nsson et al, 2012;Yu et al, 2015). The average secondary structure content for each cluster (Table S5) shows that the eight clusters can be separated into two groups, one group ( clusters 2, 5, 6, 8) with a higher a-helix propensity and another group ( clusters 1, 3, 4, 7) with a higher b-strand propensity.…”
Section: Structural Properties Of A-synuclein Conformational Ensemblementioning
confidence: 87%
“…In clusters 1, 2, and 6, the central segment of a-syn has a higher propensity to form b strand than the N-and C-terminal segments. Previous studies suggest that b-strand formation within the hydrophobic central segment may lead to oligomerization and fibril formation (Balupuri et al, 2019;Brodie et al, 2019;Graen et al, 2018;Healey et al, 2016;Jó nsson et al, 2012;Yu et al, 2015). The average secondary structure content for each cluster (Table S5) shows that the eight clusters can be separated into two groups, one group ( clusters 2, 5, 6, 8) with a higher a-helix propensity and another group ( clusters 1, 3, 4, 7) with a higher b-strand propensity.…”
Section: Structural Properties Of A-synuclein Conformational Ensemblementioning
confidence: 87%
“…In clusters 1, 2, and 6, the central segment of α-syn has a higher propensity to form β-strand than the N-and C-terminal segments. Previous studies suggest that β-strand formation within the hydrophobic central segment may lead to oligomerization and fibril formation 26,[85][86][87][88][89] . The average secondary structure content for each cluster (Table S5) shows that the eight clusters can be separated into two groups, one group (clusters 2, 5, 6, 8) with a higher α-helix propensity and another group (clusters 1, 3, 4, 7) with a higher β-strand propensity.…”
Section: Structural Properties Of α-Synuclein Conformational Ensemblementioning
confidence: 99%
“…Of note, MD generated IDP ensembles are frequently compared with experimental data and vice versa [173,174]. Naturally, since MD and the experimental techniques have their own limitations but produce complementary information, they can be used synergistically to characterize the conformational ensembles of IDPs [150,[175][176][177][178]. For example, Shrestha et al [170] recently reported how their enhanced simulation protocol was able to produce a structural ensemble of the disordered N terminal of c-Src kinase that agreed with the NMR and SAXS data, without reweighting or biasing the simulations.…”
mentioning
confidence: 99%